Efeitos da aplicação de fungos micorrízicos arbusculares (FMA) nos componentes de rendimento e resposta espectral da cultura da soja em ano de estresse hídrico - Soares, Danilo da Costa (2022)
Soybean (Glycine max) is currently the main crop produced in Brazil, standing out in terms of area, production and export. To obtain greater productivity and profitability, precision agriculture and biological agents are increasingly used. The objective of this work was to study the effect of different doses of arbuscular mycorrhizal fungi (AMF), applied at sowing, on soybean yield components and on the NDVI of the plant canopy. The work was carried out in the 2021/2022 crop in the municipality of Tapera-RS in two commercial soybean areas, the first with 13.5 ha and the second with 5.5 ha. The biological agent used was the arbuscular mycorrhizal fungus (AMF) Rhizophagus intraradices, at a concentration of 20,800 propagules per gram. The soybean cultivar used was BMX Ativa. Two experiments were implemented in different commercial areas. In experiment 1, 3 treatments were studied, T1: producer standard, consisting of the application of 250 ml ha-1 of Bradyrhizobium japonicum at a concentration of 7x109 CFU ml-1 + 200 ml ha-1 of Azospirillum brasilense at a concentration of 3x108 CFU ml -1; T2: T1 + 120g ha-1 of AMF (20,800 propagules per gram) and T3: control (without application of biologicals). The application of AMF was carried out by adding the product together with the other biological agents in the furrow inoculator. In experiment 2, 4 treatments were studied, being T1: control (without AMF application); T2: 96 g ha-1 of AMF (20% less than the standard dose); T3: 120 g ha-1 of AMF (standard dose) and T4: 144 g ha-1 of AMF (20% more than the standard dose). The inoculation of biological agents was performed manually in the seed. In the evaluation of the yield components of the soybean crop, four samples of plants, representing 4 m2 , were manually collected in each experimental plot. The number of pods per plant (NVP), the number of grains per pod (NGV), the weight of one thousand grains (PMG, g) and soybean yield (PRD, kg ha-1) were quantified. The mapping of the spatial variability of the NDVI was carried out in different phenological stages of the soybean crop. The experimental design adopted to analyze the results observed in experiment 1 was the DIC, with 4 replications. Experiment 2, by studying the application of different doses, was evaluated using simple linear regression analysis. In experiment 1, it was observed that T2 increased the thousand grain weight (PMG), representing a gain of 17.65% (27g). The other yield components did not show significant differences, although all mean values observed were higher for this treatment. In experiment 2, the use of 100 ml ha-1 of Bradyrhizobium japonicum (7x109 CFU ml-1), associated with the increase in the use of AMF (from 96 to 144 g ha-1), caused an increase in the number of pods per plant and in the number of grains per pod. The other yield components were not influenced by the treatments. The treatments studied, in both experiments, did not influence the NDVI, regardless of the soybean development stage in which this vegetation index was estimated.